The Meaning of Ending Life in Prison. (January 2017) - Liebling, Alison
There are many ways that life can end in prison. This article takes suicides, murder, and the whole life sentence as three forms of unnatural death that illustrate important features of the prison experience and that take on a special meaning in this environment. These forms of death in custody challenge the "legitimate penological purposes of imprisonment." Reflections on the importance of hope and dignity in prison are informed by this account.